2013
DOI: 10.1002/app.39482
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and properties of PCDL aliphatic hyperbranched polyurethane coatings

Abstract: The isocyanate-terminated polyurethane pre-polymer (PPU) was synthesized via the step-growth polymerization approach by using polycarbonate diol (PCDL, Mn 5 2000) and isophorone disocyanate (IPDI) as monomers, dibutyltin dilaurate (DBTDL) as the catalyst. Subsequently, the hyperbranched polyurethane (HBPU) was synthesized by graft copolymerization using PPU, hyperbranched poly(amide-ester) polyol (HPAE) and 1,4-butanediol (BDO). The molecular structure of HBPU was characterized by means of FTIR, 1 H-NMR, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The peaks at 4.84–5.0 ppm were assigned to the proton chemical shift in the ─OH groups, whereas the hydrogen atom of IPDI resonated at 0–2 ppm. All of these analyses proved that HP was successfully prepared …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The peaks at 4.84–5.0 ppm were assigned to the proton chemical shift in the ─OH groups, whereas the hydrogen atom of IPDI resonated at 0–2 ppm. All of these analyses proved that HP was successfully prepared …”
Section: Resultsmentioning
confidence: 70%
“…This phenomenon demonstrated that the introduced HP improved the thermal stability of the HWPUA films. It was due to the enhanced of compatibility between the hard and soft segments with increasing branching degree . In addition, the thermal stability of the HWPUA films at a 1.5% concentration of HP was lower that of the films at a 1% content of HP.…”
Section: Resultsmentioning
confidence: 93%
“…This was probably because the unreacted hydroxyl groups in HPAE-1 strengthened the hydrogen bond interaction of hard segments of polyurethane [ 36 ] and moved the absorption peak of C=O from a high wavenumber to a low wavenumber. The typical absorption band of OH at 3400 cm −1 was not obvious and might have overlapped with the absorption band of N-H [ 37 ]. It was manifested that waterborne polyurethane containing free hydroxyl groups (WPU-H) was synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperbranched shape‐memory polyurethane can be prepared via A 2 + B 3 approach and it offered twofold higher shape‐recovery rate compared with its linear counterpart . Isocyanate‐terminated prepolymer and hyperbranched poly(amide‐ester) polyol were used to synthesize BPU by graft copolymerization, which also showed outstanding thermal and mechanical properties …”
Section: Introductionmentioning
confidence: 99%